TOXIC MASCULINITY DALAM FILM "SEPERTI DENDAM RINDU HARUS DIBAYAR TUNTAS" (Analisis Semiotika Charles Sanders Peirce) - Damarati Rahma Widiasa, (2023)
Toxic masculinity is a social phenomenon related to distorted or deviant views of masculinity that have negative impacts on the social environment. The film "Seperti Dendam Rindu Harus Dibayar Tuntas" portrays how societal pressures regarding masculine characters are depicted through male attractiveness centered around their genitalia, the dominance of power, the suppression of emotions or sadness, and physical strength and toughness. Masculine culture is a reflection of Indonesian culture which is tough and filled with violence. This research aims to describe the phenomenon of toxic masculinity in the film "Seperti Dendam Rindu Harus Dibayar Tuntas" using a qualitative and descriptive approach and analyzing the representation of toxic masculinity using Peirce's semiotic theory by examining icons, indexes, and symbols. The results of the research show that the representation of toxic masculinity in the film is depicted through the oppression of femininity, male dominance, aggression, suppression of emotions, and sexual power. Furthermore, this research reveals that sexual power is a part of toxic masculinity by viewing male genitalia as a symbol of virility.